EVALUATING THE EFFICACY OF HOMEOPATHY IN ALLEVIATING PSYCHIATRIC CONDITIONS - Sharma, Amita; Chanchal Verma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the effectiveness of homeopathy in the treatment of psychiatric conditions, focusing on anxiety, depression, and stress-related disorders. Through a randomized controlled trial, we assessed whether homeopathy leads to significant improvements in symptom severity and overall psychological well-being. The findings reveal that homeopathy is associated with a substantial reduction in symptom severity and an improved psychiatric condition, supporting its potential role as a complementary therapeutic option for individuals with mental health challenges. The study underscores the importance of personalized treatment approaches and shared decision-making in mental healthcare. While acknowledging study limitations, these results provide valuable insights for both healthcare providers and patients seeking holistic alternatives in the management of psychiatric conditions. Further research is recommended to explore the specific mechanisms underlying homeopathy’s effects on mental health and to extend the scope of conditions studied.